A floresta consumiu a estrada: análise da propaganda da edição “Amazônia, um novo Brasil” de 1973 da Revista Manchete - Zanandrea, Clara Stedile (My University, 2022)
The objective of this work is to analyze the pages of the special edition of Manchete magazine from 1973 "Amazônia, Um novo Brasil" through the narrative discourse. For this, the emergence of the Transamazônica highway project is contextualized as a miraculous promise of national progress in an attempt to legitimize the Brazilian military dictatorship. Through the theoretical framework of ideological advertisement in Brazil and environmental advertising in the 70s, military developmental projects for the Amazon region are analyzed, highlighting the Transamazônica and the advertisements of private companies that encouraged colonization and exploitation projects in the Amazon forest. The analysis of the magazine together with other complementary sources, aligned with the bibliography, allows us to visualize how publicity and propaganda influenced the deforestation of the Amazon. Connections with the present are also presented, showing the consequences that the Transamazônica project and its dissemination and encouragement left in the present. [resumo fornecido pelo autor]
O objetivo deste trabalho é analisar as páginas da edição especial da Revista Manchete de 1973 "Amazônia, Um novo Brasil" através do discurso narrativo da mesma. Para isso, contextualiza-se o surgimento do projeto da rodovia Transamazônica como uma promessa milagrosa de progresso nacional na tentativa de legitimar a ditadura militar brasileira. Através do referencial teórico da propaganda ideológica no Brasil e da publicidade ambiental na década de 1970, são analisados os projetos desenvolvimentistas militares para a região Amazônica, destacando a Transamazônica e os anúncios de empresas privadas que incentivaram os projetos de colonização e exploração da floresta. A análise da revista juntamente com outras fontes complementares, alinhadas à bibliografia, nos permite visualizar de que modo a publicidade e a propaganda influenciaram no desmatamento da Amazônia. É também apresentado conexões com a atualidade, mostrando as consequências que o projeto da Transamazônica e sua divulgação e incentivo deixaram no presente. [resumo fornecido pelo autor]
Keywords: Propaganda; Ideologia; Rodovia Transamazônica (Brasil); Ditadura; Manchete (Revista)